Preaching Violence against Women on Television: Analysis of Critical Discourse on the Sara Mills Model (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2019)
Women are always associated with consumption contexts for reporting, especially reporting sexual violence and socioeconomic violence. The purpose of this study is to find the position of subject-objects in reporting violence against women on television and find the location of writer-reader in reporting violence against women on television. The stations studied were Metro TV and TV One. Data were collected by the method of listening, followed by using an independent, capable, record, and note-taking technique. Data analysis was performed using the matching method using the determinant element technique. Meanwhile, the approach used is a critical discourse analysis of Sara Mills model. In this study, the subject-object position was found in reporting violence against women on television. Women have always been victims of patriarchal culture. Also, the position of the writer-reader reporting on violence against women is also used as an effort to educate and raise awareness about the community related to cases of violence against women. Authentic patriarchal culture cannot be used as a basis for violence against women against men, both inside and outside the family. This is a form of discrimination against women. Also, the community needs to be fully aware of women's rights that are not fulfilled, especially in terms of security and justice before the law.